Tapering of Etanercept is feasible in patients with Rheumatoid Arthritis in sustained remission: a pragmatic randomized controlled trial. (2nd November 2022) - Bertrand, D; Stouten, V; De Cock, D; Pazmino, S; Doumen, M; de Wergifosse, I; Joly, J; Badot, V; Corluy, L; Hoffman, I; Taelman, V; De Knop, K; et al.
Abstract : Objective: In patients with rheumatoid arthritis (RA) in sustained remission, tapering of biological disease-modifying anti-rheumatic drugs can be considered. Tapering has already been investigated, but its feasibility remains to be determined. Therefore, we explored the feasibility of tapering etanercept in RA in a setting close to practice. Method: Patients with RA in 28-joint Disease Activity Score (DAS28) remission (≥ 6 months) and treated with etanercept 50 mg weekly (≥ 1 year) were included in the pragmatic 1 year open-label multicentre randomized controlled TapERA (Tapering Etanercept in Rheumatoid Arthritis) trial. Patients were assigned to continue etanercept weekly or to taper to every other week (EOW). Patients who lost remission [DAS28–C-reactive protein (CRP) ≥ 2.6] were re-escalated to etanercept weekly. The primary outcome was the proportion of patients maintaining DAS28-CRP remission for 6 months. Results: Sixty-six patients were randomized to etanercept weekly (n = 34) or EOW (n = 32). After 6 months, 26/34 patients (76%) in the weekly and 19/32 (59%) in the EOW group maintained disease control (p = 0.136). In the EOW group, 20/32 patients (63%) remained on their tapered treatment during the trial. Two patients reintroduced weekly etanercept themselves. Ten patients were re-escalated to etanercept weekly by the rheumatologist, after a median (interquartile range) interval of 3.0 (2.0–6.0) months. Among these patients, 7/10 regained remission after re-escalation, four of them at the next study visit. Conclusions: Although non-inferiority could not be demonstrated, tapering of etanercept to EOW appeared feasible in patients in sustained remission.